Effectiveness of Implementing the Non-Cash Food Assistance Program (BPNT) in Poverty Alleviation Efforts - Pratidina, Ginung; Sugiawan Putri, Yunita; Apriliani, Afmi; Wahyudin, Cecep (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2024)
The issue of poverty in Indonesia is in the spotlight, and it is immensely difficult to resolve. the Government of the Republic of Indonesia, through the Ministry of Social Affairs, has several social programs to solve poverty, one of which is the Non-Cash Food Assistance Program (BPNT). However, in implementing this program there are still several obstacles, one of which is a lack of community outreach. The purpose of this study is to determine the efficacy of the BPNT program implementation in Caringin District, Bogor Regency. n which the research data is presented according to actual events and then analyzed descriptively. The data collection techniques used interviews and documentation. According to the study's findings, implementing the Non-Cash Food Assistance (BPNT) program in Caringin District, Bogor Regency, is considered quite well implemented and effective. This assessment is based on effectiveness indicators by the theory put forward by Sutrisno (2016: 125-126). Some factors influence the effectiveness of this program's implementation, specifically the indicators of goal achievement, which can be seen in the Achievement of Goal indicators and the Real Change indicators. The indicators of understanding the program, being on target, and being on time are the factors impeding the effectiveness of this program's implementation.